Nilai Penting Agroforestri, Hutan Rakyat dan Lahan Pertanian dalam Konservasi Keanekaragaman Jenis Burung di Paliyan, Gunung Kidul, Yogyakarta - Satyawan Pudyatmoko (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Important Values of Agroforestry, Community Forest, and Agricultural Land on Conservation of Bird Diversity in Paliyan, Gunungkidul, YogyakartaAgroforestry is recognized as a land use management that capable to integrate the need of local peoples and the concern of biodiversity conservation. However, some contradictory results of studies made the importance of agroforestry on conservation of biodiversity questionable. To understand the role of agroforestry in biodiversity conservation, bird community assemblages of three land use types namely private forests, agroforestry and annual crops were compared. Single belt point count with a radius of 50 m was used to survey birds. In general species diversity in the study area was at a moderate level. Statistically, bird communities between sites did not differ significantly in term of their abundance, species composition, and diversity. It was because patch context plays more important role than patch content. However, it was found that in all community parameter agroforestry area has higher values than those of crops. Consistent with the previous studies, insectivorous birds were the most sensitive to land use changes. The conservation value of Paliyan area was relatively low, because most of species were abundant, and no species inhabit endangered status according to IUCN criteria. Implication of this research was that Paliyan area need a large-compact habitat to conserve high bird diversity.